From the Editors - Lee, Tom (Academy of Management Journal, 2002)
A letter from the editor is presented. The editor announces the formation of a new editorial board featuring Don Bergh, Dov Eden, and Sara Rynes. He also discusses the importance of the peer-review process, which is used in the submission and publication process. There is also a call for volunteers for ad hoc reviewers to compensate for the mass submission of papers.